Quality Attributes of Cheese Produced from Goat’s Milk Supplemented with Coconut Milk - Elijah, Aniekpeno Isaac; Edem, Victor Ephraim; Harrison, Iniobong Ime (Journal of Food Technology Research, 2020)
Quality attributes of cheese produced from goat’s milk supplemented with coconut milk was studied. Fresh goat milk was blended with coconut milk at varying proportions of 90:10; 80:20; 70:30; and 50:50. A 100% goat milk was used as control. Result showed that increase in the proportion of coconut milk (10-50%) resulted in significant (p<0.05) effect in quality parameters of cheese. Values ranged from 0.20-0.33% TTA; 6.40-6.69 pH. TSS declined from 1.14% in the control sample to 0.56% at 50% coconut milk substitution. The yield of cheese increased from 22.55 - 30.69% with increased coconut milk. Proximate composition of cheese was also influenced by increased proportion of coconut milk. Protein, ash, fibre and fat contents of cheese ranged from 12.94-14.49%; 1.28-2.08%; 0.03-1.79% and 15-40.41% respectively. Conversely, carbohydrate content of cheese decreased with increased coconut milk. Mineral contents of cheese showed maximum value of 74.03 mg/100g potassium, 41.60 mg/100g sodium and declined with decrease in coconut milk content, while magnesium content was highest (8.10 mg/100g) in cheese produced using 10% coconut milk supplementation. Potassium content of cheese was least (59.27 mg/100g) in control sample, but increased with increase coconut milk content. Microbial analysis showed that the product was safe for consumption. The blend of 90:10% of goat milk and coconut milk substitution was most preferred by panelists in terms of sensory parameters.